Impact of operational systems on supplier's response under performance-based contracts - Mirzahosseinian, H. (2014)
Performance-based contract has developed into a new service strategy in after-market operations that aims to compensate for performance outcomes. One of the key components of a performance-based contract is performance measure that is affected by factors such as base stock, reliability and response time. To achieve a desired performance level, the supplier has to improve the component reliability and the repair time. The component reliability in a repairable part inventory system is a function of the number of operational systems and the service capacity. In this research, we consider a single echelon repairable part inventory system and conduct a parametric analysis to evaluate the impact of the total number of systems on the supplier's decisions under a performance contract. The results show that the numbers of systems plays a key role on the supplier's response when the customer uses the average number of backorders as the negative incentive.